Social needs screening in primary care: A tool in the fight for health equity? - H. Painter; E. Parry; L. McCann; A. Dehn Lunn; J. Ford (Elsevier, 2024)
Progress on addressing health inequalities is slow and in many places around the world the gap between the privileged and the disadvantaged is widening. This is driven largely by an unfair and unequal distribution of the social determinants of health. While upstream policy and agenda commitment is needed to improve social determinants of health at a population level, healthcare also has a role. Currently social information is sporadically collected and used in healthcare. Improving our understanding of social problems is crucial in targeting services and to reduce the overreliance on area-level measures of deprivation. This has the potential to improve patient care as well as more accurately capture socio-economic disadvantage. Here we argue that there is a role for primary care in screening for social needs to help address inequalities.Social needs screening, more commonly used in North America than Europe, aims to systematically collect social information in health and care settings. Healthcare professionals ask patients about social issues including employment, finances, housing, education and social isolation and this information is used to prompt referral to community services to address any need identified.Social needs screening has potential to address negative impacts of social determinants of health at an individual and population level. Providing a reliable measure of social need, screening gives healthcare professionals an opportunity to tailor and improve quality of care for patients and offer individualised support. It has been shown to improve individual social and health outcomes and positively impact healthcare utilisation. At a population level, social needs screening can improve the data on social determinants of health and therefore support policy makers and service delivery leaders to target resources and services more effectively to the communities most in need. Implementing social needs screening must take account of local healthcare service capacity and available community resources but where sustainable, effective programmes can be introduced, the potential benefits are manifold.While primary care alone cannot solve the root causes of health inequalities, we argue it could be a powerful actor in the fight for health equity.